Mobile phone use and risk of brain neoplasms and other cancers: prospective study. - Benson, V; Pirie, K; Schüz, J; Reeves, G; Beral, V; Green, J (2013)
BACKGROUND: Results from some retrospective studies suggest a possible increased risk of glioma and acoustic neuroma in users of mobile phones. METHODS: The relation between mobile phone use and incidence of intracranial central nervous system (CNS) tumours and other cancers was examined in 791,710 middle-aged women in a UK prospective cohort, the Million Women Study. Cox regression models were used to estimate adjusted relative risks (RRs) and 95% confidence intervals (CIs). Women reported mobile phone use in 1999 to 2005 and again in 2009. RESULTS: During 7 years' follow-up, 51,680 incident invasive cancers and 1,261 incident intracranial CNS tumours occurred. Risk among ever vs never users of mobile phones was not increased for all intracranial CNS tumours (RR = 1.01, 95% CI = 0.90-1.14, P = 0.82), for specified CNS tumour types nor for cancer at 18 other specified sites. For long-term users compared with never users, there was no appreciable association for glioma (10+ years: RR = 0.78, 95% CI = 0.55-1.10, P = 0.16) or meningioma (10+ years: RR = 1.10, 95% CI = 0.66-1.84, P = 0.71). For acoustic neuroma, there was an increase in risk with long term use vs never use (10+ years: RR = 2.46, 95% CI = 1.07-5.64, P = 0.03), the risk increasing with duration of use (trend among users, P = 0.03). CONCLUSIONS: In this large prospective study, mobile phone use was not associated with increased incidence of glioma, meningioma or non-CNS cancers.